Extravagance and Reportage as Forms of Creation and Understanding. An Academic Frottage - Płuciennik, Jarosław (Zagadnienia Rodzajów Literackich, 2022)
In this editorial introduction to the issue, the author and editor of the journal “Zagadnienia Rodzajów Literackich. Formy kultury i teorii” tries to use several concepts to deal with eleven texts gathered in the issue. The main theoretical problem arises because the issue is not focused on a particular subject. Instead, the author of the introduction claims that most articles can be described using a concept of extravagance and the other ones — applying a concept of reportage. All writings in this editorial are described metaphorically as frottage and parergon. The first article is characterized using a generic concept of extravaganza and eccentrics. The second article is a description of the uses magic and modern enchantment as understood by Max Weber, the third — rococo and militancy. The fourth article is about translating on the margins, the fifth on multilingual postcolonial translation, the sixth on post-human analysis of national myths. The second part of the issue is more devoted to reportage in the context of gonzo journalism and storytelling and quality research, as well as crypto philosophy. The final point is about understanding as a passerby. Frottage and parergon are the most crucial theoretical concepts used in this editorial introduction. In the humanities, such concepts can be seen as political through and through.